Intermittent fasting interventions for treatment of overweight and obesity in adults: a systematic review and meta-analysis. (February 2018) - Harris, Leanne; Hamilton, Sharon; Azevedo, Liane B.; Olajide, Joan; De Brún, Caroline; Waller, Gillian; Whittaker, Vicki; Sharp, Tracey; Lean, Mike; Hankey, Catherine; Ells, Louisa
ABSTRACT: Objective: To examine the effectiveness of intermittent energy restriction in the treatment for overweight and obesity in adults, when compared to usual care treatment or no treatment. Introduction: Intermittent energy restriction encompasses dietary approaches including intermittent fasting, alternate day fasting, and fasting for two days per week. Despite the recent popularity of intermittent energy restriction and associated weight loss claims, the supporting evidence base is limited. Inclusion criteria: This review included overweight or obese (BMI ≥25 kg/m 2 ) adults (≥18 years). Intermittent energy restriction was defined as consumption of ⩽800 kcal on at least one day, but no more than six days per week. Intermittent energy restriction interventions were compared to no treatment ( ad libitum diet) or usual care (continuous energy restriction ∼25% of recommended energy intake). Included interventions had a minimum duration of 12 weeks from baseline to post outcome measurements. The types of studies included were randomized and pseudo-randomized controlled trials. The primary outcome of this review was change in body weight. Secondary outcomes included: i) anthropometric outcomes (change in BMI, waist circumference, fat mass, fat free mass); ii) cardio-metabolic outcomes (change in blood glucose and insulin, lipoprotein profiles and blood pressure); and iii) lifestyle outcomes: diet, physical activity, quality of life and adverse events. Methods: A systematic search was conducted from database inception to November 2015. The following electronic databases were searched: MEDLINE, Embase, CINAHL, Cochrane Library, ClinicalTrials.gov, ISRCTN registry, and anzctr.org.au for English language published studies, protocols and trials. Two independent reviewers evaluated the methodological quality of included studies using the standardized critical appraisal instruments from the Joanna Briggs Institute. Data were extracted from papers included in the review by two independent reviewers using the standardized data extraction tool from the Joanna Briggs Institute. Effect sizes were expressed as weighted mean differences and their 95% confidence intervals were calculated for meta-analyses. Results: Six studies were included in this review. The intermittent energy restriction regimens varied across studies and included alternate day fasting, fasting for two days, and up to four days per week. The duration of studies ranged from three to 12 months. Four studies included continuous energy restriction as a comparator intervention and two studies included a no treatment control intervention. Meta-analyses showed that intermittent energy restriction was more effective than no treatment for weight loss (−4.14 kg; 95% CI −6.30 kg to −1.99 kg; p ⩽ 0.001). Although both treatment interventions achieved similar changes in body weight (approximately 7 kg), the pooled estimate for studies that investigated the effect of intermittent energy restriction in comparison to continuous energy restriction revealed no significant difference in weight loss (−1.03 kg; 95% CI −2.46 kg to 0.40 kg; p = 0.156). Conclusions: Intermittent energy restriction may be an effective strategy for the treatment of overweight and obesity. Intermittent energy restriction was comparable to continuous energy restriction for short term weight loss in overweight and obese adults. Intermittent energy restriction was shown to be more effective than no treatment, however, this should be interpreted cautiously due to the small number of studies and future research is warranted to confirm the findings of this review.